TEKNOLOGI PIRAMIDA GEN TANAMAN PADI DALAM MENGHADAPI PERUBAHAN IKLIM GLOBAL - Fatimah Fatimah; Joko Prasetiyono; Sustiprijatno Sustiprijatno (BERITA BIOLOGI, 2020)
In the attempt to maintain and hopefully increase national rice production, it is necessary to prepare agriculture sector in facing the impacts of climate change, land degradation, dry land, flooding, slowing production, and population growth rate. Adaptation efforts play an important role in ensuring the sustainability of food security. The development of adaptive rice varieties to abiotic stresses specifically drought and submergence stresses are expected to minimize damage, survive stress, continue to grow and produce. Development of Inpari 30 rice varieties tolerant to submergence to drought tolerant to have a broader spectrum of tolerance through marker-assisted backcrossing methods with the gene pyramid approach. The development of new variety using Inpari 30 as the background is one of the applications of pyramiding gene in Indonesia. Combining conventional breeding with molecular markers and phenotypic selection (drought and submergence) is expected to produce rice lines tolerant to drought and submergence with stabil yields and accelerate the homozygosity of the genome in the third generation. This is an alternative solution to dealing with climate change to support the national food security program.